Estructura y Potencialidad de Distintos Tipos de Bosque Nativo en el Sur de Chile - Brun, Ronald (Bosque (Valdivia), 1975)
In tre Andes mountains within the province of Valdivia, where the mayority of the native forest species of Southern Chile occur, a study was conducted concerning structur and potential of the forest. Stratifaying the species into two groups according to tolerance and occurrence at different altitudes, forest types are established which are also appropriate for photointerpretation. Employing sufficiently large sample plots (1/10 há.) in virgin forests, it is possible to differentiate phases in the type by mean diameter. These phases represent very homogenes substrate which can be utilized to improve presicion of forest inventories. Diameter distributions of these phases are represented by hiperbolic equations and they can be dynamic stages of development of virgin forests. Finaly, a growth analysis of the types based on meassurements of diameter increment and stem analysis shows a quite distinct potencial in the phases with values which frecuently surpace 10 m3/há. year.